Case Report: Effect of testicular adenomatoid tumors on testicular endocrine function in children - Li, Yan; Zhao, Junfeng; Chen, Yi; Zhang, Jing; Chen, Hehe (Frontiers in Endocrinology, 2025)
Adenomatoid tumors, rare benign mesothelial neoplasms primarily involving the reproductive tract, account for 30% of paratesticular masses and predominantly localize to the epididymal head. Although typically diagnosed in adults (mean age: 33 years), pediatric cases are exceptionally rare. Conservative excision with testicular preservation is optimal, yet diagnostic ambiguity often leads to unnecessary orchidectomy. A 5.2-year-old boy presented with asymptomatic left testicular enlargement. MRI identified a 13 × 14 mm heterogeneous mass on the lateral testis. Intraoperative frozen section analysis suggested benign/low-grade malignancy, confirmed postoperatively as a parenchymal adenomatoid tumor via immunohistochemistry. A 5-year prospective study assessed testicular function through serial measurements of serum hormones [follicle-stimulating hormone (FSH), luteinizing hormone (LH), testosterone, inhibin B (INHB), and anti-Müllerian hormone (AMH)] and bilateral testicular volume (TV). Our findings were as follows: Left TV exceeded age-adjusted norms by 2.1-fold (4.2 mL vs. 2.0 mL), contrasting with right TV at 0.5× mean (1.0 mL). AMH declined to a nadir (2.1 ng/mL) at 48 months, recovering to 3.8 ng/mL by 60 months. INHB reached minimal levels (45 pg/mL) at 6 months postresection, peaking at 128 pg/mL by study endpoint. FSH (1.2–1.5 IU/L) and testosterone (T, 0.15–0.18 ng/mL) remained prepubertal, while LH (0.3–0.5 IU/L) persisted near lower normative limits. This study demonstrates the progressive decline of Sertoli cell function in pediatric adenomatoid tumor survivors, detectable through longitudinal monitoring of INHB, AMH, and TV. The 2.1-fold compensatory hypertrophy in the affected testis suggests adaptive mechanisms requiring further investigation. Conservative resection guided by frozen section analysis prevents orchidectomy, while biomarker surveillance enables early detection of testicular dysfunction for timely intervention.